Polyarteritis nodosa presenting with necrotising appendicitis and hepatic aneurysm rupture - Necdet ÖZÇAY; Kemal ARDA; Tonguç SUGÜNEŞ; Deniz ÖZDEMİREL and Gülden AYDOĞ and Fuat ATALAY and Musa AKOĞLU (Turkish Journal of Gastroenterology, 2019)
-